Taxonomy of the fern genus Hypodematium (Pteridophyta: Hypodematiaceae) from Japan - Fan, Xue-Ping; Gao, Xin-Fen; Zhang, Li-Bing (Phytotaxa, 2020)
A taxonomic study of Hypodematium (Hypodematiaceae) from Japan is presented. Three species are recognized including H. faurei, H. glanduloso-pilosum, and H. ryukyuense (sp. nov.).